Prognostic value of serum concentration of matrix metaloproteinase-9 in patients in acute period of spontaneous supratentorial intracerebral hemorrhage - Kuznietsov, А. A.; Кузнєцов, Антон Анатолійович (My University, 2021)
Objective: to evaluate the informative value of serum concentration of matrix metalloproteinase (MMP)-9 within the determination of the short-term prognosis in patients in the acute period of spontaneous supratentorial intracerebral hemorrhage (SSIСH) on the ground of conservative treatment. Materials and methods. A prospective, cohort, comparative study was conducted in 105 patients in the acute period of SSICH on the ground of conservative treatment. The level of neurological deficit was assessed using of the Full Outline of Unresponsiveness Coma Scale, the Glasgow Coma Scale, and the National Institutes of Health Stroke Scale. The visualization of cerebral structures was performed by computed tomography. On the 1st and 5th day from the admission, laboratory blood samples were taken and then serum concentrations of MMP-9 were determined by enzyme-linked immunosorbent assay. Early neurological deterioration and unfavorable outcome of the acute period of SSICH (modified Rankin scale grade 4–6 on the 21st day of the disease) were registered as combined clinical endpoints. Statistical processing of the results was carried out with the help of correlation analysis, logistic regression analysis, ROC-analysis. Results. Patients with unfavorable clinical course and unfavorable outcome of the acute period of SSICH had a higher serum concentration of MMP-9 on the 1st day from the admission, and this marker was directly correlated with the secondary intraventricular hemorrhage volume (R=0.40, p<0.01) and total volume of intracranial hemorrhage (R=0.29, p<0.01). It was determined that the assessment of serum MMP-9 concentration along with neuroimaging indicators (midline shift severity, secondary intraventricular hemorrhage volume) as part of the developed multi-predictor logistic regression model allows to verify individual risk of early neurological deterioration (AUC±SE (95% confidence interval)=0.93±0.03 (0.86–0.97), p<0.0001). Conclusion. Serum MMP-9 levels in patients with SSICH on the 1st day from admission is an informative additional parameter for prediction of early neurological deterioration on the ground of conservative treatment. Оцінити інформативність сироваткової концентрації матриксної металопротеїнази (ММП)-9 у визначенні короткострокового прогнозу у пацієнтів у гострий період спонтанного супратенторіального внутрішньомозкового крововиливу (ССВМК) на тлі консервативної терапії. Об’єкт і методи дослідження. Проведено проспективне когортне порівняльне дослідження за участю 105 пацієнтів у гострий період ССВМК на тлі консервативної терапії. Оцінку рівня неврологічного дефіциту здійснювали за шкалою коми Full Outline of UnResponsiveness, шкалою коми Глазго та шкалою інсульту Національних інститутів здоров’я США. Візуалізацію церебральних структур здійснювали методом комп’ютерної томографії. У 1-шу та на 5-ту добу з моменту госпіталізації проводили забір лабораторних зразків крові з подальшим визначенням сироваткових концентрацій ММП-9 методом імуноферментного аналізу. У якості комбінованих клінічних кінцевих точок реєстрували раннє клініконеврологічне погіршення та несприятливий вихід гострого періоду ССВМК (4–6 балів за модифікованою шкалою Ренкіна на 21-шу добу захворювання). Статистичну обробку результатів здійснювали інструментами кореляційного аналізу, логістичного регресійного аналізу, ROC-аналізу. Результати. Пацієнти з несприятливими варіантами перебігу та виходу гострого періоду ССВМК відрізнялися більш високою сироватковою концентрацією ММП-9 в 1-шу добу з моменту госпіталізації, при цьому цей показник прямо корелював з обсягом вторинного внутрішньошлуночкового крововиливу (R=0,40, p<0,01) та загальним обсягом інтракраніальної геморагії (R=0,29, p<0,01). Встановлено, що оцінка вмісту ММП-9 в сироватці крові разом із нейровізуалізаційними показниками (вираженість латеральної дислокації серединних структур мозку, обсяг вторинного внутрішньошлуночкового крововиливу) у складі розробленої мультипредикторної логістичної регресійної моделі дозволяє визначати індивідуальний ризик раннього клініко-неврологічного погіршення з точністю 90,5% (AUC±SE (95% довірчий інтервал)=0,93±0,03 (0,86–0,97), р<0,0001). Висновок. Вміст ММП-9 в сироватці крові пацієнтів із ССВМК в 1-шу добу з моменту госпіталізації є інформативним додатковим показником для прогнозування раннього клініко-неврологічного погіршення на тлі консервативної терапії.
Прогностична цінність сироваткової концентрації матриксної металопротеїнази-9 у пацієнтів у гострий період спонтанного супратенторіального внутрішньомозкового крововиливу
Keywords: intracerebral hemorrhage; matrix metalloproteinase-9; prognosis; внутрішньомозковий крововилив; матриксна металопротеїназа-9; прогноз